Improved stenosis outcome in stroke‐free sickle cell anemia children after transplantation compared to chronic transfusion. (20th November 2020) - Verlhac, Suzanne; Gabor, Flaviu; Paillard, Catherine; Chateil, Jean‐François; Jubert, Charlotte; Petras, Marie; Grevent, David; Brousse, Valentine; Petit, Philippe; Thuret, Isabelle; Arnaud, Cécile; Kamdem, Annie; et al.
Summary: We report here the 3‐year stenosis outcome in 60 stroke‐free children with sickle cell anaemia (SCA) and an abnormal transcranial Doppler history, enrolled in the DREPAGREFFE trial, which compared stem cell transplantation (SCT) with standard‐care (chronic transfusion for 1‐year minimum). Twenty‐eight patients with matched sibling donors were transplanted, while 32 remained on standard‐care. Stenosis scores were calculated after performing cerebral/cervical 3D time‐of‐flight magnetic resonance angiography. Fourteen patients had stenosis at enrollment, but only five SCT versus 10 standard‐care patients still had stenosis at 3 years. Stenosis scores remained stable on standard‐care, but significantly improved after SCT ( P = 0·006). No patient developed stenosis after SCT, while two on standard‐care did, indicating better stenosis prevention and improved outcome after SCT.